An exploratory study of influences on vulnerabilities to family violence among Vietnamese wives who marry South Korean men - Park, Suyeon (Critical criminology, 2017)
This article describes an exploratory study of why Vietnamese women who migrate to marry South Korean men are vulnerable to abuse. Inductive qualitative analysis of data from 22 Vietnamese wives who experienced abuse reveals inconsistencies in their expectations and their Korean husbands’ and in-laws’ expectations about their roles and influence in their Korean families and their provision of assistance to their Vietnamese families. A marriage broker system in both Vietnam and Korea supports these inconsistent expectations. Abuse and control result when Korean husbands and in-laws act to enforce their expectations of the women’s role in the family and to prevent their leaving the home.